Current practice for primary headache disorders and perspectives on peripheral nerve blocks among emergency physicians in Canada: A national survey. Issue 4 (10th April 2022) - Patel, Dilan; Taljaard, Monica; Yadav, Krishan; James, Daniel; Perry, Jeffrey J.
Abstract: Objective: This national postal survey aimed to examine Canadian emergency physicians' practice patterns with respect to drug treatment and perspectives on peripheral nerve blocks. Background: The treatment of primary headache disorders in the emergency department is variable. Methods: We surveyed 500 emergency physicians listed in the Canadian Medical Directory according to a modified Dillman's method: an initial invitation was followed by up to four reminders to nonresponders. Physicians were asked questions regarding their frequency of medication administration and perspectives toward peripheral nerve blocks. Results: Of 500 mailed surveys, 468 were delivered and 179 physicians responded (response rate = 38.2%). The majority of physicians were men (92/144, 63.9%); 80.6% (116/144) had been in practice for greater than or equal to 10 years with 50.7% (75/148) in a community or district general teaching hospital. Commonly used pharmacotherapies for primary headaches were intravenous dopamine receptor antagonists (69%), co‐administration of ketorolac and a dopamine receptor antagonist (54.2%), intravenous fluid boluses (54%), nonsteroidal anti‐inflammatory drugs (NSAIDs) alone (53.5%), and acetaminophen (51.4%). Only 80 of 144 physicians (55.6%) reported previous experience with peripheral nerve blocks (95% confidence interval [CI] = 48%–65%). The majority (68/80, 85.0%) agreed peripheral nerve blocks are safe and 55.1% (43/78) agreed they are effective. The vast majority (118/140, 84.3%) would consider peripheral nerve blocks as a first‐line treatment option given sufficient evidence from a future trial (95% CI = 78%–90%). Conclusion: NSAIDs alone, as well as dopamine receptor antagonists with or without ketorolac are commonly used for primary headache in Canadian emergency departments. A large proportion of physicians have never used a peripheral nerve block in their practice; among those who have experience with peripheral nerve blocks, the majority find them safe and effective. The majority of respondents would consider peripheral nerve blocks as a first‐line treatment option given sufficient evidence from a future trial.